ANALYSIS OF THE PPF VALUE DEPENDENCE ON THE FUEL BURNUP - Lily Suparlina; Purwadi Purwadi; Kunihiko Nabeshima (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2022)
The RSG-GAS reactor has been operated in a safe and reliable manner for about 35 years since it commenced in operation in 1987 to serve radioisotopes production, NAA, neutron beam experiments, material irradiation, and reactor physics experimental activities as well as training. PPF value is necessary to determine by calculation because it is impossible to determine by experiment and also has a strong relation to the operation safety. The paper is intended to analyze the PPF values of the RSG-GAS reactor core as a function of burn up. The analysis is using WIMSD-5B/BATAN-3DIFF computer codes calculation. The result shows that the PPF values are significantly different for each burn-up or energy in MWD. The result also shows that the BATAN-3DIFF code accurately determines the PPF values of the RSG-GAS reactor core and supports the safety of reactor operation.